Potential roles of gut microbial tryptophan metabolites in the complex pathogenesis of acne vulgaris - Huang, Yukun; Liu, Lu; Hao, Zhenyu; Chen, Lingna; Yang, Qian; Xiong, Xia; Deng, Yongqiong (Frontiers in Microbiology, 2022)
Acne vulgaris is a chronic inflammatory skin disease referring to multiple complex pathogenesis such as over-proliferation of Cutibacterium acnes (C. acnes), abnormal hyperkeratosis, excessive sebaceous secretion, and increased androgen sensitivity, which still could not fully explain the mechanism of this common disease. Recently, the disorder of gut microbiota (GM) was supported by increasing evidence to contribute to the development of acne vulgaris. As is well known that many of these effects are mediated by GM-derived metabolites and tryptophan (Trp), an essential aromatic amino acid, is considered important among many metabolites in the crosstalk between gut microbiota and the host in both health and disease state. In this review, we gather the most recent advances concerning the important role of Trp metabolism in mediating both skin inflammation and function of sebaceous glands, as well as gut permeability, which will facilitate a better understanding of the pathogenesis of acne vulgaris and open therapeutic opportunities.